2021
DOI: 10.1002/ab.21962
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing and externalizing symptoms and aggression and violence in men and women

Abstract: Literature linking aggressive behavior across internalizing and externalizing disorders support the co‐occurrence of aggression and various mental health diagnoses. However, research has yet to examine relationships between aggression and dimensional psychopathology models that cut across diagnostic boundaries (e.g., internalizing, externalizing composites) and capture shared liability across common disorders. The role of gender has also been largely ignored in prior work, despite evidence that men and women m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 51 publications
7
16
2
1
Order By: Relevance
“…On the other hand, men show higher rates of externalizing disorders, namely, impulse control and substance abuse ( Needham & Hill, 2010 ), and their response to stress primarily involves the fight-or-flight response ( Taylor et al, 2000 ). In our study, male students reported higher aggressiveness, a behavior often associated to externalizing disorders ( Mendez et al, 2021 ). Our study is the first to report aggressiveness in male university students in Mexico during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, men show higher rates of externalizing disorders, namely, impulse control and substance abuse ( Needham & Hill, 2010 ), and their response to stress primarily involves the fight-or-flight response ( Taylor et al, 2000 ). In our study, male students reported higher aggressiveness, a behavior often associated to externalizing disorders ( Mendez et al, 2021 ). Our study is the first to report aggressiveness in male university students in Mexico during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 50%
“…This study addresses several important knowledge gaps. In Aim 1, we sought to replicate and extend Mendez et al (2021) by examining (a) unique and interactive effects of internalizing dimension (i.e., depression, anxiety, negative emotionality) and externalizing dimension composites (i.e., antisocial behavior, substance use, disinhibition) in relation to self-directed (i.e., non-suicidal self-injury, suicide ideation, suicide attempts) and other-directed aggression. We used a multi-method approach to assess aggression, using both interviewbased and questionnaire data for self-directed aggression, and questionnaire, interview, and laboratory data to inform indices of other-directed aggression.…”
Section: Present Studymentioning
confidence: 99%
“…Men relative to women show more prominent externalizing traits (Mendez et al, 2021b). Studies have also reported sex differences in behavioral and neural reactivities to reward and punishment.…”
Section: Sex Differences In Neural Responses To Reward and Punishmentmentioning
confidence: 99%
“…The literature is less consistent with respect to sex differences in internalizing traits. Overall, women appeared to show more internalizing traits than men (Malhotra and Shah, 2015;Mendez et al, 2021a;Padgaonkar et al, 2020) and the patterns of sex differences remained stable across the lifespan (van Loo et al, 2021). On the other hand, another study noted no sex differences in any internalizing measures of the child behavior checklist in typically developing youth (Padgaonkar et al, 2020).…”
Section: Sex Differences In Externalizing and Internalizing Traitsmentioning
confidence: 99%